Faktor Risiko Lingkungan yang Berhubungan dengan Kasus Leptospirosis pada Manusia: a Systematic Review - Rusyda Ihwani Tantia Nova; Dhimas Herdhianta (Buletin Keslingmas, 2025)
Leptospirosis is an infectious disease caused by pathogenic organisms in the genus Leptospira, which are widespread across various ecosystems, especially in tropical climates such as Indonesia. The incidence of this disease is higher in humid areas than in temperate climates. The incidence of leptospirosis ranges from 0.1-1 per 100,000 per year in temperate climates and 10-100 per 100,000 in humid tropical climates. This study aims to identify the dominant environmental factors that commonly cause leptospirosis across regions through a systematic review. Articles were searched for in five data sources using three keywords, namely environment, leptospirosis, and risk factors. Based on the review results, the environmental factors that influence the incidence of leptospirosis are vegetation and wildlife habitats, flooding, the presence of rodents, the presence of livestock and agriculture, humidity, and water sources. This emphasises the importance of environment-based interventions in prevention strategies, such as improving sanitation, waste management, and environmental monitoring. Based on this understanding of environmental factors, early detection programs and public education can be expanded more effectively to reduce the incidence of leptospirosis in the future.